Combating Teaching Failure: An Interdisciplinary Approach to Educating the Next Generation and Producing Market–Ready Graduates - Henson, Cassandra R. (Journal of Interdisciplinary Studies in Education, 2019)
Preparing future professionals in any industry requires specific education and detailed training early on in the academic process ideally, prior to the influences of the work environment. Many schools and programs offer standard industry courses but much more needs to be accomplished, as the scope and management of private industry and public service continues to expand. In some cases, the current standard pedagogical practices have failed to prepare students for the workplace, an environment that is ever-changing due to advancing technologies, political agendas and societal pressures. By teaching in a silo and being focused on one content area, much of the educational system is providing a disservice to students by not removing the blinders. Sector lines have become increasingly blurred, so the education of future professionals must now take an interdisciplinary approach to successfully navigate this new environment. Market-ready graduates must have the ability to successfully navigate the private, public and nonprofit sectors. This research will suggest several possible avenues to an interdisciplinary pedagogy model, by examining the core competencies of three ‘flagship’ sector degrees. By combining traditional academic pedagogy with cross-sector topics, we may reduce instances of failed academic preparation and may in fact encourage the next generation of leaders to be even more dynamic than those who’ve come before, successfully converting theory to practice.